Effects of steel pile corrosion on permeability of hydraulic barriers. Issue 8 (24th October 2018) - Minder, Pascal; Plötze, Michael; Hughes, Joseph; Puzrin, Alexander M
Abstract : An increasing economic interest leads to construction on old landfills and waste deposits, raising questions about potential contamination of groundwater due to installation of piles through clay barriers. The current consensus in the geotechnical practice, that penetration of clayey hydraulic barriers by driven steel piles with closed conical tips should not cause pollution of the underlying aquifers, is challenged in this paper. Consolidometer and flow-column tests on clays with iron-rich pore fluid were performed for the assessment of pile corrosion effects on hydraulic barriers. Based on the results of these tests, a constitutive model for the coupled chemomechanical behaviour was modified to account for different pore-fluid chemistry and incorporated into a finite-element code to solve the problem of iron diffusion originating from a corroding source in a case study on groundwater pollution. The combined action of diffusion, corrosion and increased convection resulted in an overall increased transport rate and therefore a significantly earlier arrival of critical concentrations of the pollutant in the aquifer that was initially protected by a hydraulic barrier. Once this barrier is perforated by foundation piles subjected to corrosion, small concentrations can arrive in the aquifer up to four times earlier than implied by the initially low hydraulic conductivity.